PENGARUH DATUAK RAJO SAMPONO TERHADAP ETNIS NIAS DI NAGARI KETAPING PADANG PARIAMAN 1994 - 2022 - yulika zetimorina; Abdul Salam (Puteri Hijau : Jurnal Pendidikan Sejarah, 2023)
This research is a historical study that discusses influence of Datuak Rangkayo Rajo Sampono or better known as Rajo Sampono on the presence of ethnic Nias in Nagari Ketaping Padang Pariaman in 1994 – 2022. The aim of the research is to analyze the influence of Datuak Rajo Sampono on the existence of Nias in Nagari Ketaping in 1994 – 2022. This study uses the historical method which consists of four steps, namely heuristics (of source collection), verification (source criticism), verification (source criticism), interpretation and historiography (writing). The Nias people in Nagari Ketaping were Nias who were invited by the rule of Ketaping, namely Datuak Kasupian in 1901. The results of the existence of Rajo Sampono had a big influence on the existence of the Nias ethnicity in Nagari Ketaping. The ethnic Nias who live in nagari Ketaping are haighly appreciated and well received by the local community where Rajo Sampono gives the title of Datuak to the Nias people who live in Ketaping also carry out the limbago dituang custom, that is, fulfill the requirements that are set a minimum to become a minagkabau Nagari child.